Benthic foraminifera as ecological indicators in the Tunda Island Waters, Serang District, Banten Province, Indonesia - ISNI NURRUHWATI; FACHRI ARDIANSYAH; YUNIARTI; LINTANG PERMATA SARI YULIADI; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nurruhwati I, Ardiansyah F, Yuniarti, Yuliadi LPS, Partasasmita R. 2020. Benthic foraminifera as ecological indicators in the Tunda Island Waters Serang District, Banten Province, Indonesia. Biodiversitas 21: 3142-3148. Coral reef communities all across Southeast Asia are experiencing intense pressures from extensive tourism and massive coastal development. A prediction regarding coral reefs’ capacity to recover is a necessity since it is constantly exposed to damaging events such as mass bleaching and increased erosion. Tunda Island (which is highly rich in biodiversity and include coral reefs, mangrove forests, seagrass, and algae meadows) was sampled at 10 different sites in August 2019. Coral reefs are highly influenced by ecological factors such as temperature variability, salinity, DO, and pH. The assessments were conducted using the FORAM Index (FI) to accurately predict the capacity of coral reefs to recover based on relative abundances of symbiont-bearing larger benthic foraminifera in reef sediments. The FI values ranged from 3.7 to 7.9 with a median of 4.7 and the average of 5 indicates that the water quality should support the recovery of reefs by reef-building corals and symbiont-bearing larger benthic foraminifers. The lowest FI value sampled was recorded from a site with extensive human activities (FI=3.4), while the highest one was recorded from a site with minimal to none human activities (FI=7.9), which indicates that the deterioration of water quality is caused by wastes from tourism activities near the coastal area.